2013
DOI: 10.4183/aeb.2013.11
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Urinary Bladder Morphology, Mast Cell Population and Estrogen Receptor Alpha Expression Following Ovarectomy and Chronic Estrogen Replacement Therapy in Albino Rats

Abstract: Context. The inflammatory disorders of the urinary bladder represent one of the most frequent disorders associated with hormonal unbalances caused by menopause. The involvement of estrogens and mast cells in this complex mechanism mediated by neuro-hormonal pathway is well known, but the pathogenesis through which the hormonal deprivation is affecting the Estrogen Receptor expression and is predisposing to urinary bladder inflammatory changes is still argued.Objective. To determine the structural changes assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…However, in this study the number of leukocytes significantly decreased, which agrees with reports for urinary bladder biopsies in which it has been shown that oestrogen privation is associated with inflammation [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in this study the number of leukocytes significantly decreased, which agrees with reports for urinary bladder biopsies in which it has been shown that oestrogen privation is associated with inflammation [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…All this causes a decrease of Doderlein’s bacilli, an increase of vaginal pH, and a decrease of the vaginal humidity, finally finishing in atrophy, all of which are corrected with oestrogen use [ 12 ]. In the rat urinary bladder, it has been shown that the lack of oestrogens is associated with atrophy of vesical epithelium and inflammation [ 13 ], which increases the risk of local infections [ 14 ] and vesical activity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, ER-a receptors are expressed in the adenohypophysis, breast, uterus, uterine tract and vagina, while ER-b receptors are expressed in the urinary tract, ovary, thyroid, skin, lung and thymus [18,33]. Due to the large number of oestrogenic receptors in the vagina and vulva, the latter will react promptly to the action of oestrogens, both natural and synthetic [1,2,8].…”
Section: Introductionmentioning
confidence: 99%
“…While Kim et al (2001) was showing the negative feedback between estrogens and mast-cells cytokine production (TNFa and IL 6). Lucan et al (2013) are associating alterations in rats mainly with the hormonal deprivation due to prior ovarectomy, represented by growth in number of the bladder mast cells, atrophy of the urothelium and amplification of the expression of estrogen receptors-a from the urothelium. Other authors, cited in an actual review of the current bibliography, maintain the controversy: mastcells estrogen activation.…”
Section: Discussionmentioning
confidence: 99%